(untitled) (Applied Biological Research, 2020)
Cadmium is a toxic metallic element that, if present in high concentrations in soil, poses severe human health risks through intake of contaminated agricultural produces. A pot experiment was conducted in a net house to assess nutrient uptake by rice (Oryza sativa L.) in cadmium-contaminated soil amended with biochar. Six cadmium levels (0, 20, 40, 60, 80 and 100 mg kg-1) and three levels of biochar @ 0, 20 and 40 t ha-1, respectively, were taken. Results indicated that nutrient content and its uptake decreased with increasing levels of soil cadmium. Nutrient content and its uptake were significantly high in soils amended with biochar. Also, the nitrogen and phosphorus contents and their uptake weremore in grains; whereas potassium content and its uptake were more in rice straw. Biochar may be usedto alleviate the toxic effect of cadmium in cadmium contaminated soils.